Penile emergencies: two years experience at our centre - Muppirala, Lakshmi Ramesh; Gaddam, Yaswanth Kumar; Jain, Udit; Bathalapalli, Ravi Theja (International Journal of Research in Medical Sciences, 2024)
Background: Many men with penile injuries opt out of medical treatment for ethical or psychological reasons, which means the true incidence is likely substantially lower than reported. Urgent medical attention is usually required for acute penile illnesses, which are rare but serious. A vascular, viral, or trauma-related event is usually to blame. Methods: The study was carried out at Narayana medical college in Nellore for a duration of two years, from January 2022 to April 2024.There were four groups vascular group with priapism and spontaneous penile gangrene (n=9) and those with penile fractures, degloving injuries, amputations, and entrapment (n=16) were part of the infected group, whereas patients with penile myiasis were part of the trauma group. The last group consisted of four patients who had paraphimosis. Results: The results showed that 60% of patients who had penile fractures within 6 hours presented for treatment. Every single patient has a torn tunica and one of them even has urethral involvement. Idiopathic causes 62.5% of the eight cases of priapism, and 37.5% of patients presented within six hours. Aspiration with intra-cavernous phenylephrine was the. If they fail to respond, employ the grey hack and water shunt techniques. Conclusions: The incidence of penile injuries is underreported; patients may appear to healthcare providers far later than necessary, and this is largely attributable to psychological and ethical factors, such as shame and fear. However, early and rapid management led to better outcomes.